1978
DOI: 10.1111/j.1365-2605.1978.tb00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of LHRH and Its Agonists on Testicular Gonadotrophin Receptors and Spermatogenesis in the Rat

Abstract: Treatment of adult male rats with the potent LHRH agonists [D‐Leu6, des‐Gly‐NH210]LHRH ethylamide or [D‐Ala6. des‐Gly‐NH210]LHRH ethylamide led to a marked reduction of testicular LH and prolactin receptor levels accompanied by decreased plasma testosterone levels and testis, seminal vesicle and prostate weight. Maximal inhibitory effects were seen at a dose of 50 ng. After a single injection, maximal inhibitory effects were seen at 2–4 days with return toward normal levels at later time intervals. Similar res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
1

Year Published

1980
1980
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(35 citation statements)
references
References 23 publications
1
32
1
1
Order By: Relevance
“…5) are consistent with those of Sherins (33); hCG alone suppressed endogenous FSH production but led to no change in sperm counts. In addition, we found no evidence that hCG, administered chronically in this moderately supraphysiological dosage, led to testicular regression as has been reported with high dosage hCG and LH-releasing hormone administration to animals (34,35). It may be that a higher dosage of hCG is required to demonstrate this effect in men.…”
Section: Discussioncontrasting
confidence: 47%
“…5) are consistent with those of Sherins (33); hCG alone suppressed endogenous FSH production but led to no change in sperm counts. In addition, we found no evidence that hCG, administered chronically in this moderately supraphysiological dosage, led to testicular regression as has been reported with high dosage hCG and LH-releasing hormone administration to animals (34,35). It may be that a higher dosage of hCG is required to demonstrate this effect in men.…”
Section: Discussioncontrasting
confidence: 47%
“…Similar results were obtained by Labrie et al (1978), who injected 100ng of [D-Ala] In contrast, we found that the Ka values for testicular LH/hCG and LHRH receptors changed during LHRHa administration. The Ka value for the LH/hCG receptor was consistently increased during LHRHa treatment, while that for the LHRH receptor was decreased between weeks 2 and 4 of treatment.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, GnRH-A do not suppress basal LH levels in intact male rats during chronic treatment. With a variety of regimens (i.e., D-Leu6-GnRH, ng [57]; D-Ala6-GnRH; 100 ng-1 yg [10,58,59]; D-Tryp6-GnRH, 0.001-1 ,g [12]; Bus-erelin, 0.034-34 yg, or GnRH itself, 0.034-340 ug/d [11]), basal LH was unchanged or increased in intact animals, while suppression occurred exclusively in castrates. Only with very high dose GnRH (i.e., 200 ug q.d.…”
Section: Discussionmentioning
confidence: 99%